Thermal stability and performance evaluation of hitec molten salt for high-temperature energy storage applications - Kousik Suraparaju, Subbarama; Samykano, Mahendran; Narayana Namasivayam, Satesh Narayana; Kadirgama, Kumaran; Ramasamy, Devarajan (EDP Sciences, 2024)
The quest for advanced materials in thermal energy storage (TES) has become paramount in a world grappling with pressing demands for sustainable and reliable energy solutions. Among these materials, molten salts have emerged as up-and-coming contenders, owing to their exceptional thermal properties and wide operational temperature ranges. HITEC, a eutectic blend of sodium nitrate, sodium nitrite, and potassium nitrate, distinguishes itself as a superior choice due to its unique amalgamation of favorable thermal characteristics. This comprehensive review delves into the thermal properties of HITEC molten salt and its manifold applications in thermal energy storage, illuminating its potential as a pivotal element in addressing contemporary global challenges. The review examines HITEC's specific heat capacity, thermal conductivity, and thermal stability, presenting critical insights into its efficacy as a TES medium. Such comprehension fosters the advancement of Sustainable Development Goal 7. The article explores strides made in HITEC-based TES systems, underscoring inventive engineering approaches and burgeoning technologies that bolster progress towards Sustainable Development Goal 9. Furthermore, the article discusses challenges associated with HITEC molten salts, such as corrosion and material compatibility issues, and investigates ongoing research efforts to overcome these limitations. A comparative evaluation of HITEC with other molten salt mixtures elucidates its competitive advantages. This review consolidates knowledge about HITEC molten salt for thermal energy storage applications, providing valuable perspectives for researchers, engineers, and policymakers dedicated to advancing sustainable energy technologies. The review underscores the pivotal role of HITEC molten salt in advancing thermal energy storage technologies, directly influencing the achievement of several SDGs.